Criterios para determinar un caso De violencia contra la mujer “por su condición de tal” - Rivas La Madrid, Sofia (2022)
The author emphasizes that not all aggression against a woman should be presumed carried out under the gender motive, since this must be accredited. It develops the concepts of Violence against women because of their gender, structural discrimination, gender stereotypes and gender approach. Based on the conceptual development, it analyzes how to apply the gender approach and identify gender stereotypes, by developing a practical case of violence against women due to their condition as such, typically subsumed in the crime of attempted femicide. Finally, the author develops the proposal in order to identify the position of dominance in the interpersonal dynamics between victim/perpetrator.